Extraction of Natural Dye from Walnut Bark and its Dyeing Properties on Wool Yarn. Issue 4 (3rd July 2016) - Ali Khan, M.; Shahid-Ul-Islam; Mohammad, F.
Abstract: The present study was undertaken to extract natural colorant from walnut bark and to explore its dyeing potential on wool fiber. The effect of potassium aluminum sulfate mordant concentration on dyeability, color characteristics, and fastness properties has been studied using CIEL*a*b* system. Twenty-seven shades were developed for their color characterizations and fastness properties using pre-mordanting technique. The results from the dyeing showed that potassium aluminum sulfate mordanted as well as unmordanted dyed samples exhibit satisfactory color and fastness properties.